Competitividade na agroindústria cooperativa láctea no estado de Mato Grosso - Santos, Débora Borges dos (2017)
Based on the potential of dairy cooperatives of Mato Grosso, this study was motivated by the search for means to improve the organizational capacity of these companies, and it also aimed to present guidelines that, respecting the economic and social aspects of cooperative enterprises, support the decisions and contribute to the improvement of its management, in order to achieve and sustain new levels of competitiveness. Four of the seven cooperatives that make up the dairy cooperative agro-industry in Mato Grosso participated in the study. The tools that supported the diagnosis were the model of Porter's five competitive forces and the SWOT analysis. Strategies for competitive positioning were analyzed from the perspective of Porter's generic strategies. The study of multi-cases was based on assumptions, analyzes and qualitative results, based on a literature review of the central themes: competition and cooperation, as well as field research, whose data collection was done through the application of structured questionnaire and interview with open questions. The main forces for competition in the sector analyzed are the bargaining power of the supplier, holder of the raw material; and consumer power, which by concentrating their purchases on large supermarket chains, increase the bargaining power of these channels. The cooperative organization has been observed as an important strategy applied in defense to the strength of the supplier. Among the guidelines we have pointed out, the following guidelines stand out: the adoption of measures to strengthen relations between the cooperative and the milk producers; the loyalty of the cooperative personnel through communication channels that transmit information and innovations, understanding the heterogeneity of the group and aiming at their capacitation for better management of rural properties, and the explicitation of strategies to align actions among the agents involved and to simplify the decision-making process.